2019
DOI: 10.1111/pan.13734
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of difficult intravenous access among children presenting for procedures requiring anesthesia at a tertiary academic medical center

Abstract: CORRESPONDENCE procedures, has been reported to be safe in pediatric patients, 1,2 but trauma to the wall of an artery may lead to the development of a pseudoaneurysm. 3 Our case suggests that when the deep venipuncture is performed, particularly in children with low body weight, ultrasound guidance should be used to reduce the chances of puncture damage to blood vessels, nerves, and other tissues. Once the arteries are pierced, they need to be properly treated to prevent the formation of pseudoaneurysms such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…This study, as well as research done by Petroski et al 10 reported that difficult intravenous access was most common at very young ages, 9 especially in the 7- to 11-month-old group. 9 Although groin access was not attempted in this patient, ultrasound examination of the neck and groin veins should be performed to determine vessel patency. Furthermore, these patients should also be thoroughly examined for cardiovascular abnormalities.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study, as well as research done by Petroski et al 10 reported that difficult intravenous access was most common at very young ages, 9 especially in the 7- to 11-month-old group. 9 Although groin access was not attempted in this patient, ultrasound examination of the neck and groin veins should be performed to determine vessel patency. Furthermore, these patients should also be thoroughly examined for cardiovascular abnormalities.…”
Section: Discussionsupporting
confidence: 78%
“…According to Patak et al, 9 obesity is associated with significantly more difficulty in establishing intravenous access in children. This study, as well as research done by Petroski et al 10 reported that difficult intravenous access was most common at very young ages, 9 especially in the 7- to 11-month-old group. 9 Although groin access was not attempted in this patient, ultrasound examination of the neck and groin veins should be performed to determine vessel patency.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound of the neck with Color Doppler detected an echogenic structure in the right neck with "to and fro" flow pattern and "yin yang" color pattern, classic for a pseudoaneurysm (C) [Colour figure can be viewed at wileyonlinelibrary.com] procedures, has been reported to be safe in pediatric patients, 1,2 but trauma to the wall of an artery may lead to the development of a pseudoaneurysm. 3 Our case suggests that when the deep venipuncture is performed, particularly in children with low body weight, ultrasound guidance should be used to reduce the chances of puncture damage to blood vessels, nerves, and other tissues. Once the arteries are pierced, they need to be properly treated to prevent the formation of pseudoaneurysms such as effective partial pressure bandaging, and routine follow-up with ultrasound to permit early detection.…”
Section: Iatrogenic Common Carotid Pseudoaneurysm In a Neonatementioning
confidence: 92%
“…First, we developed and disseminated a DIVA algorithm identifying risk factors for DIVA and outlining a goal of no greater than 3 attempts to establish PIV access with or without ultrasound ( Figure S1a, Supplemental Digital Content 1, http://links.lww.com/PQ9/A253 ). 6 This algorithm did not explicitly state DIVA predictors, as these are well established (younger age, higher BMI, increased comorbidities). Instead, the algorithm focused on providing a target (IV access within 3 attempts) and encouraged earlier ultrasound use.…”
Section: Methodsmentioning
confidence: 99%
“…We based this algorithm on a previous study published by our group, finding that DIVA occurred in 5.3% of anesthetics in our practice and was associated with several risk factors and prolonged time to surgical incision, notably following the third attempt. 6 Second, we implemented a training program for attending anesthesiologists, consisting of 2 group learning sessions with simulation practice using a training model (Blue Phantom, CAE Healthcare Sarasota, Fla.) and 1:1 training and mentorship in the operating room using the technique described by Gopalasingam et al, 16 as this was the most common technique employed by those proficient in ultrasound-guided PIV placement at our institution. A volunteer group of anesthesiologists known to be proficient in ultrasound-guided PIV access (defined as greater than 90% chance of successful IV placement using ultrasound) before the intervention was sought to act as trainers.…”
Section: Methodsmentioning
confidence: 99%